Perbandingan Latihan Otot Inti dengan Latihan Pergelangan Kaki dalam Meningkatkan Kelincahan Pemain Sepak Bola - Dimas Agusta; I Made Jawi; Wahyuddin Wahyuddin; Putu Astawa; I Nyoman Adiputra; Susy Purnawati (Syntax Corporation Indonesia, 2021)
Sport is a needs for human being, sport that early introduced in a young people giving a good effect for physical condition, psychology, and social. Along the growth and development of young soccer player, makes some transformation to their physical condition and to have an impact to their body proportional and decreasing of coordination and agility. To support dribbling skill, a soccer player need to have a good agility. The stability of your core muscle and your ankle affected the agility. The objective of this research is to explain the effect of core muscle stability exercise and ankle stability exercise for dribbling agility, and to compare both of exercises for dribbling agility on soccer player age 14-17 years old. This research used quasi-experimental methods. Subject divided into 2 group, that is Group 1 with core stability exercise intervention and Group 2 with ankle stability exercise intervention. The research will be done in 6 weeks, and 3 times a week. The dribbling agility measurement in this study used Dribbling Agility Test (DAT). From 14 subject, was obtained the difference average of dribbling agility value from the group with core muscle stability exercise was 1.8 ± 1.3 second (p-value=0.010, p<0.05), and the difference average of dribbling agility value from the group with ankle stability exercise was 2.29 ± 1.37 second (p-value=0.005, p<0.5). There is no difference between the group in increasing dribbling agility with p-value=0.477 (p>0.05). Both exercises shown improvement in each group in increasing dribbling agility with no difference between the group.